The impacts of studying abroad: Evidence from a government-sponsored scholarship programme in Brazil - Otávio Canozzi Conceiç\~ao; Rodrigo Carvalho Oliveira; André Portela Souza (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper investigates the impact of the Science without Borders (Ciência sem Fronteiras) (CSF) programme on participants' post-graduation enrolment, employment, and entrepreneurship. The programme was launched in 2011 to increase students' human capital and interest in science and postgraduate education studies through a substantial increase in scholarships for Brazilians to carry out part of their undergraduate studies abroad. We exploit variation in the approval rate across CSF selection calls for the same destination country and year and combine 17 public and private administrative records to track CSF candidates' outcomes up to eight years after the call. The main results suggest that the programme did not achieve its goals of increasing approved student enrolment in postgraduate education programmes in Brazil. Even though the programme could have improved student skills and acted as a market signalling, we do not find effects on the probability of working in the formal labour market, or as formal entrepreneurs. Using detailed data from one top university, we show that approved students graduate more often, but take longer to graduate, which may have negative impacts on their labour market outcomes. Finally, although we cannot rule out that students moved to a foreign country after the programme, we show that the likelihood of this event may have decreased over time.
Keywords: H00; I23; J01; 330; study abroad; education; Brazil; Ciência sem Fronteiras